Identification of current sustainable forest management (SFM) policy targets formulated in national forest-focused policies and strategies in Europe - Lier, Markus (Natural Resources Institute Finland, Luke, 2016)
The demands on forests for wood and energy production are foreseen to increase in the future. This has triggered in new forest-related policies and strategies at different political levels and across different sectors (e.g. reviewed EU Bioeconomy strategy in 2017). This study analyses on how sustainable forest management (SFM) targets have been formulated and set in national forest-focused policies and strategies for 19 European countries. Results show that SFM policy targets formulated in national forest-focused policies and strategies represent the ecological and socio-economic framework of each country. The results show also that SFM forest-focused policy targets may contradict, e.g. increasing use of wood versus increasing the area of protected forests, which may result in an increase of forest area not available for wood supply, unless the area of forest is not increased as well.
Keywords: national SFM policy targets; national forest focused policies and strategies